Dampak Penggunaan Smartphone Terhadap Kedisiplinan Siswa Kelas III dan V Tahun Pelajaran 2023/2024 - Bagas Oktobera Sanyata; Nela Rofisian; Putri Zudhah Ferryka (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The aim of this research is to find out whether the use of smartphones can influence student discipline at Pandes State Elementary School. This type of research is quantitative. Quantitative research is research that uses numerical counting techniques with the help of Microsoft Excel and SPSS version 27. The data collection techniques used by researchers are in the form of interviews, observation, questionnaires and documentation. Data collection techniques through validation levels carried out by experts, interviews, namely using interview guidelines or grids along with interview sheets, observations using guidelines or observation grids along with observation sheets, questionnaires or questionnaires using guidelines or questionnaire grids along with questionnaire sheets or questionnaires, and documentation. This research is a sample study in which the researcher will take a sample of 20 students consisting of lower and upper classes, namely only class III and class V at Pandes State Elementary School. The analysis technique uses a validity test, a reliability test uses Cronbach's Alpha while the hypothesis test uses a simple linear regression test. The research results obtained have an influencing impact on the use of smartphones on student discipline. 57.9% from smartphone impacts while 42.1% from other impacts not included in this study. The results of the calculations above use the latest version of the SPSS application, namely SPSS 27. This impact is in the form of a positive impact on student discipline. Because the results of the simple regression calculation, namely Ha, are declared acceptable. So it can be concluded that the use of smartphones has a positive impact on students.